2008
DOI: 10.1111/j.1365-2389.2008.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulating mineral N release and greenhouse gas emissions by mixing groundnut residues and rice straw under field conditions

Abstract: Groundnut as a pre-rice crop is usually harvested 1-2 months before rice transplanting, during which much of legume residue N released could be lost. Our objectives were to investigate the effect of mixing groundnut residues (GN, 5 Mg ha À1 ) with rice straw (RS) in different proportions on: (i) regulating N dynamics, (ii) potential microbial interactions during decomposition, and (iii) associated nitrous oxide and methane emissions at weekly intervals during the lag phase until rice transplanting (i, ii) or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 35 publications
2
24
4
Order By: Relevance
“…The average CH 4 fluxes from wet-season and dry-season rainfed rice fields were 54 % and 16 %, respectively, that of continuously flooded fields, lower than the IPCC values of 80 % and 40 % for flood-prone rainfed and drought-prone rainfed rice fields, respectively (IPCC, 1997). Compared with the previous results (Yan et al, 2005a), the greater average CH 4 flux from wet-season rice fields was mainly attributed to the observed high fluxes from rainfed rice fields in Thailand and India (Kaewpradit et al, 2008;Kantachote et al, 2016;Rath et al, 1999). However, the CH 4 flux from deep water rice, only 6 % that of continuously flooded rice fields, remained less reliable due to the lack of sufficient observational data in the current analysis.…”
Section: Effects Of Controlling Variablescontrasting
confidence: 74%
“…The average CH 4 fluxes from wet-season and dry-season rainfed rice fields were 54 % and 16 %, respectively, that of continuously flooded fields, lower than the IPCC values of 80 % and 40 % for flood-prone rainfed and drought-prone rainfed rice fields, respectively (IPCC, 1997). Compared with the previous results (Yan et al, 2005a), the greater average CH 4 flux from wet-season rice fields was mainly attributed to the observed high fluxes from rainfed rice fields in Thailand and India (Kaewpradit et al, 2008;Kantachote et al, 2016;Rath et al, 1999). However, the CH 4 flux from deep water rice, only 6 % that of continuously flooded rice fields, remained less reliable due to the lack of sufficient observational data in the current analysis.…”
Section: Effects Of Controlling Variablescontrasting
confidence: 74%
“…Therefore, it is imperative that management strategies are identified that could ensure synchrony between N release from cowpea residues and uptake by subsequent crops while minimizing N 2 O emissions. Mixing residues of different C:N ratios can increase temporary N immobilisation and prolong N mineralisation (Handayanto et al 1997;Schwendener et al 2005;Vityakon et al 2000) and alter N 2 O emission (Kaewpradit et al 2008). The high C:N ratio cereal residue can provide large amounts of labile C to enhance microbial activity, immobilisation of inorganic residue and/or soil-N and lower N 2 O emission compared to sole incorporation of low C:N ratio legume residues (Handayanto et al 1997;Vityakon et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Regarding the type of crop residue, a larger CH 4 emission rate could be expected from soils under legume crops than under grass, due to the faster decomposition rate mainly attributed to the lower C/ N ratio and, therefore, greater labile C production for methanogenesis (Kaewpradit et al, 2008). A plausible explanation for the absence of difference between crop residue types in terms of CH 4 soil emissions is the interval of 25 days between the time of crop residue application and transplanting of rice seedlings to the pots.…”
Section: Soil Ch 4 Emissionmentioning
confidence: 99%
“…These are the main processes related to the N 2 O generation in soil (Khalil et al, 2004). Consequently, legume species could exacerbate N 2 O emissions from flooded rice production systems (Aulakh et al, 2001;Kaewpradit et al, 2008), but there is little evidence regarding the effect of different residue management systems on the emission of these greenhouse gases (Shan et al, 2008;Kaewpradit et al, 2008). This greenhouse study aimed to evaluate (i) the influence of crop residues (legume and grass species) and their management (incorporated into the soil or left on the soil surface) on CH 4 and N 2 O emissions from an Albaqualf soil under flooded rice, (ii) their influence on soil reduction and interaction with the soil CH 4 and N 2 O emission, and (iii) the contribution of these gases to the partial global warming potential, in equivalent CO 2 , taking their respective warming potentials into account.…”
Section: Introductionmentioning
confidence: 99%